The rising [compact disc] - Springsteen, Bruce (Columbia, 2002)
The Boss delivers with this touching and heartfelt album that reaches out to all of America in the aftermath of 9/11. Features the intimate songs The Rising; Lonesome Day; Empty Sky; and My City of Ruins.